PERSISTENCE AND REINTERPRETATION OF TRADITIONAL ARCHITECTURAL PRINCIPLES IN KENADSA - Meriem Benlahbib; Naima Hadj Mohamed; Djamel Alkama (International Journal of Innovative Technologies in Social Science, 2024)
This study explores the persistence and reinterpretation of traditional architectural principles in contemporary dwellings in Kenadsa, a Saharan city in southwestern Algeria. The problem studied is how traditional architectural elements, such as inner courtyards and the use of local materials, are maintained in modern buildings despite the influence of urbanization, industrialization, and social change. The objective is to understand how these principles are adapted to meet contemporary requirements, particularly in terms of thermal comfort, energy efficiency and respect for cultural identities. To achieve this objective, a mixed methodology was adopted. It combines a thorough review of the literature with case studies on contemporary housing incorporating traditional elements. Architectural analyses, field visits, surveys and qualitative interviews with architects, planners and residents have provided rich and varied data. These data were then analyzed in a comparative manner to assess the persistence of traditional principles. The results show that, although modernist designs are predominant, there is a significant effort to integrate traditional architectural elements into contemporary houses. For example, the move from open patios to central enclosed halls illustrates an adaptation of vernacular principles to modern needs while maintaining the energy efficiency and thermal regulation of traditional buildings. These results highlight the dynamic co-habitation between cultural heritage and innovation in Kenadsa’s architecture, demonstrating that traditional principles can evolve and adapt to contemporary contexts while maintaining their relevance.